2001
DOI: 10.1287/ijoc.13.3.210.12632
|View full text |Cite
|
Sign up to set email alerts
|

Fast Heuristics for the Maximum Feasible Subsystem Problem

Abstract: G iven an infeasible set of linear constraints, finding the maximum cardinality feasible subsystem is known as the maximum feasible subsystem problem. This problem is known to be NP-hard, but has many practical applications. This paper presents improved heuristics for solving the maximum feasible subsystem problem that are significantly faster than the original, but still highly accurate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
83
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(84 citation statements)
references
References 19 publications
0
83
0
1
Order By: Relevance
“…Altogether, y ij = 1 − x ij . By using the above results, we can rewrite the objective function (9) by splitting the case of e ij = 0 from the case of e ij = 1. Denote with E ∈ {0, 1} n×n the following diagonal matrix.…”
Section: Correction Of the Data Recordsmentioning
confidence: 99%
See 1 more Smart Citation
“…Altogether, y ij = 1 − x ij . By using the above results, we can rewrite the objective function (9) by splitting the case of e ij = 0 from the case of e ij = 1. Denote with E ∈ {0, 1} n×n the following diagonal matrix.…”
Section: Correction Of the Data Recordsmentioning
confidence: 99%
“…3. Inconsistencies are selected by selecting irreducible infeasible subsystems (IIS, see also [1,9,10,32]) by using a variant of Farkas' lemma (see e.g. [31]), while redundancies are detected by finding implied inequalities.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally it has been shown that it does not admit a polynomial time approximation scheme (unless P = NP) [3]). Some exact and heuristc algorithms have been proposed (see, e.g., [24], [10], [2], [25]), but none of these has been tested on problems of the dimensions with which we are concerned. For more details and additional references the reader is referred to [4], [25] or [16].…”
Section: Dealing With Infeasibility and Insufficient Memorymentioning
confidence: 99%
“…Our experience with problems of different sizes is that typically between 5 and 20 iterations are necessary to find an optimal solution, and up to 60 if the problem is infeasible. The number of iterations obviously depends on the particular choice of right-hand side in (10). In particular, the number of iterations will depend on the choice of the constant ρ in (8).…”
Section: Parallel Performancementioning
confidence: 99%
“…Many published researches h infeasibility, [1,[10][11][12][13], however, there are few papers deal with infeasibility resolution [14][15][16]. One of the useful references is [17].…”
Section: Introductionmentioning
confidence: 99%